Access to education - Beteille, Andre (2008)
Indian universities face a difficult and uncertain future. They must expand and multiply, and they must be socially inclusive. But if they are to retain credibility as centres of science and scholarship, they must also be selective in appointments and admissions and in the award of degrees. - Reproduced.
Keywords: Education